Deoxyglucose-resistant mutants of Neurospora crassa: isolation, mapping, and biochemical characterization. - Allen, K E (1989)
Neurospora crassa mutants resistant to 2-deoxyglucose have been isolated, and their mutations have been mapped to four genetic loci. The mutants have the following characteristics: (i) they are resistant to sorbose as well as to 2-deoxyglucose; (ii) they are partially or completely constitutive for glucose transport system II, glucamylase, and invertase, which are usually repressed during growth on glucose; and (iii) they synthesize an invertase with abnormal thermostability and immunological properties, suggesting altered posttranslational modification. All of these characteristics could arise from defects in the regulation of carbon metabolism. In addition, mutants with mutations at three of the loci lack glucose transport system I, which is normally synthesized constitutively by wild-type N. crassa. Although the basis for this change is not yet clear, the mutants provide a way of studying the high-affinity system II uncomplicated by the presence of the low-affinity system I.